Escoamento bifásico líquido-gás em golfadas com leve mudança de direção - Parra, Víctor Enrique Llantoy (2013)
Two-phase, liquid-gas flow mixtures are usually transported through pipes stretching over irregular terrains. Those irregularities disturb the flow characteristics, thus predicting the behaviour of such disturbed flows becomes necessary. The present work introduces an experimental and numerical study on the effects of a slight direction change on the behaviour of a gas-liquid two-phase slug flow. The aforementioned study was carried out in a 1” (26 mm), 5.8-m long transparent pipe section followed by a +7o inclined pipe (3.4-m long) transporting air-water two-phase mixtures at different flow rates. This experimental rig was designed and assembled in the LACIT/UTFPR labs. Resistive sensors and pressure transducers were installed at four testing positions in the pipe, designated as metering stations. Void fractions, bubble translational velocities, in situ pressures and the lengths of the liquid slug and the bubble region – as well as the fluctuations of those flow parameters – were measured at these stations. A classical slug tracking approach was applied as the numerical scheme. That approach attempts at simultaneously solving the one-dimensional mass and momentum conservation equations for each instant of time, resulting in coupled system of pressure-velocity equations. A mathematical model to predict the flow behaviour at the pipe position where the change in direction occurred was developed and implemented. The equations of such mathematical model were implemented as source terms in the slug tracking model. The numerical results were compared to the experimental data using averaged results and frequency distribution of the data collected at the metering stations, and a good agreement was observed.